Pterostilbene, an active constituent of blueberries, enhances innate immune activation and restricts enterovirus D68 infection - Yang, Qingran; Li, Huili; Li, Zhaoxue; Yang, Jiaxin; Zhang, Zhe; Zhang, Lili; Guo, Haoran; Wei, Wei (Frontiers in Immunology, 2023)
Enterovirus D68 (EV-D68) is a globally re-emerging respiratory pathogen implicated in outbreaks of severe respiratory illnesses and associated with acute flaccid myelitis. However, effective vaccines or treatments for EV-D68 infections remain scarce. We demonstrated that the active constituent of blueberries, pterostilbene (Pte), and its major metabolite, pinostilbene (Pin), facilitated innate immune responses in EV-D68-infected human respiratory cells. Pte and Pin treatment clearly relieved EV-D68-triggered cytopathic effects. Importantly, both Pte and Pin disrupted viral RNA replication (EC50 rank from 1.336 to 4.997 µM) and infectious virion production in a dose-dependent manner, without cytotoxicity at virucidal concentrations. Pte- or Pin-treated respiratory cells did not show any influences on EV-D68 entry but showed substantially decreased viral RNA replication and protein synthesis. Finally, we showed that Pte and Pin broadly suppressed the replication capacity of circulating EV-D68 strains isolated from recent pandemics. In summary, our results suggest that Pte and its derivative, Pin, enhance host immune recognition of EV-D68 and suppress EV-D68 replication, which represents a promising strategy for antiviral drug development.